2003
DOI: 10.1038/nrg1204
|View full text |Cite
|
Sign up to set email alerts
|

The origin of new genes: glimpses from the young and old

Abstract: Genome data have revealed great variation in the numbers of genes in different organisms, which indicates that there is a fundamental process of genome evolution: the origin of new genes. However, there has been little opportunity to explore how genes with new functions originate and evolve. The study of ancient genes has highlighted the antiquity and general importance of some mechanisms of gene origination, and recent observations of young genes at early stages in their evolution have unveiled unexpected mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
704
5
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 832 publications
(755 citation statements)
references
References 116 publications
12
704
5
13
Order By: Relevance
“…The K a /K s ratio should be 1 for pseudogenes, <1 for genes subject to functional constraint and >1 for genes subject to strong positive darwinian selection 13 . But because new genes have rapid changes in protein sequences 4,8 , they may have more similar values of K a and K s than their parental genes, bringing the K a /K s ratio closer to 1. Therefore, the K a /K s ratio of a new gene may not be a powerful measure of functionality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The K a /K s ratio should be 1 for pseudogenes, <1 for genes subject to functional constraint and >1 for genes subject to strong positive darwinian selection 13 . But because new genes have rapid changes in protein sequences 4,8 , they may have more similar values of K a and K s than their parental genes, bringing the K a /K s ratio closer to 1. Therefore, the K a /K s ratio of a new gene may not be a powerful measure of functionality.…”
mentioning
confidence: 99%
“…Although gene fission is a common process in prokaryotes 2 and has been reported in eukaryotes 4,21 , the mechanism involved was unknown. The process by which mkg originated identified the first such mechanism: duplication followed by complementary partial degeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that gene duplication and exaptation from TEs are the main mechanisms to generate GSGs, however, it is likely that there are other origin mechanisms forming the majority of SSGs, such as exon shuffling, lateral gene transfer, gene fusion/fission, and de novo origination [22], which remain poorly understood for LSGs.…”
Section: Discussionmentioning
confidence: 86%
“…Gene duplication is generally thought to be an important means for many genes to evolve new functions and helps the evolution of developmental programs in a variety of organisms [22,23]. The integration of Transposable Elements (TEs) into the genome to form new functions is also a general phenomenon, which has been shown in the analyses of Procedure for identifying lineage-specific genes within C. elegans.…”
Section: Origin Analysis Of Lsgsmentioning
confidence: 99%